New knowledge on major genetic switches that took place during the evolution of modern buffaloes. - CGIAR Research Program on Livestock (2020)
Whole genome re-sequencing revealed adaptation prior to the divergence of buffalo subspecies. Better understanding of the origins of buffalo genome diversity may guide ex-situ conservation priorities, contribute to studies of genetic variants for economic and ecologically important traits; and feed into admixture analysis to determine an individual animal's breed composition.